An exploration of learning needs: identifying knowledge deficits among hospitalized adults with heart failure - Erika Raines; Sabrina L. Dickey (AIMS Press, 2019)
The current study examined the learning needs of hospitalized patients with chronic heart failure (CHF) by identifying their current CHF self-care behaviors and knowledge levels, while identifying relationships between clinical variables, and their learning needs. A descriptive, cross-sectional design was utilized to examine a convenience sample of 42 hospitalized patients with CHF. Self-care behaviors and knowledge levels were measured using the Self Care of Heart Failure Index V. 6.2, and the Japanese Heart Failure Knowledge Scale. Descriptive statistics were used to describe the learning needs and sociodemographic data and Pearson product moment correlation examined relationships between the learning needs and clinical variables. The mean scores of self-care were 38.6% (maintenance), 41.6% (management) and 17.8% (confidence). The participant's mean knowledge level score was 74.9%. Multiple CHF hospital readmissions had a significant negative correlation with CHF knowledge scores (r = −0.358, p < 0.05), suggesting the lower the knowledge score, the higher the prevalence of CHF readmissions. There were significant positive correlations between self-care maintenance (r = 0.525, p < 0.05), management (r = 0.435, p < 0.05), confidence (r = 0.366, p < 0.05), knowledge level (r = 0.752, p < 0.05) and not living alone. Thus, indicating that living with family support is correlated with better self-care and greater knowledge. The presence of multiple comorbidities revealed significant positive correlations (p < 0.05) with self-care scores (maintenance [r = 0.391], management [r = 0.438], and confidence r = 0.504), indicating a higher number of comorbidities, yielded lower self-care behaviors. Findings revealed poor self-care behaviors in all three areas (maintenance, management, confidence). These findings suggested that patients had difficulty implementing knowledge into self-care. By identifying knowledge deficits and contributing factors to suboptimal self-care, the chronic care model can be used as a guideline for ideal CHF education and management. Improving self-care behaviors can be obtained by initiating an active engagement between health care teams and the patient.